Anthropometric and physical characteristics of English academy rugby league players - Till, K.; Tester, E.; Jones, B.; Emmonds, S.; Fahey, J.; Cooke, C. (The Journal of Strength and Conditioning Research, 2014)
The purpose of the present study was to evaluate the anthropometric and physical characteristics of English academy rugby league players by annual-age category (under 16s-under 20s) and between backs and forwards. Data were collected on 133 academy players over a 6-year period (resulting in a total of 257 assessments). Player assessments comprised of anthropometric (height, body mass, sum of 4 skinfolds) and physical (vertical jump, 10- and 20-m sprint, estimated VO2max via the yo-yo intermittent recovery test level 1, absolute 1 repetition maximum [1RM], and relative squat, bench press, and prone row) measures. Univariate analysis of variance demonstrated significant (p kleiner/gleich 0.05) increases in height, body mass, vertical jump, absolute, and relative strength measures across the 5 annual-age categories (e.g., body mass: under 16s = 75.2 ± 11.1, under 20s = 88.9 ± 8.5 kg; vertical jump: under 16s = 45.7 ± 5.2, under 20s = 52.8 ± 5.4 cm; 1RM bench press: under 16s = 73.9 ± 13.2, under 20s = 114.3 ± 15.3 kg). Independent t-tests identified significant (p kleiner/gleich 0.05) differences between backs and forwards for anthropometric (e.g., under 16s body mass: backs = 68.4 ± 8.6, forwards = 80.9 ± 9.7 kg) and physical (e.g., under 19s 20-m sprint: backs = 3.04 ± 0.08, forwards = 3.14 ± 0.12s; under 18s relative squat: backs = 1.65 ± 0.18, forwards = 1.51 ± 0.17 kg/kg) characteristics that were dependent on the age category and measure assessed. Findings highlight that anthropometric and physical characteristics develop across annual-age categories and between backs and forwards in academy rugby league players. These findings provide comparative data for such populations and support the need to monitor player development in junior rugby league players.